2005
DOI: 10.2214/ajr.184.4.01841340
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-Occluded Retrograde Transvenous Obliteration of Gastric Varices with Gastrorenal Shunt: Long-Term Follow-Up in 78 Patients

Abstract: B-RTO is an effective method for gastric varices with gastrorenal shunt and provides lower recurrence and bleeding rates. We believe that B-RTO can become a standard treatment for gastric varices with gastrorenal shunt, although treatment of worsened esophageal varices may be necessary after B-RTO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
286
3
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(308 citation statements)
references
References 30 publications
16
286
3
3
Order By: Relevance
“…GV have a lower bleeding rate than esophageal varices, 3,4 but once ruptured, GV tend to bleed profusely as they have greater blood flow compared with esophageal varices. The cumulative risk for bleeding from gastric fundal varices is 16%, 36%, and 44% at 1, 3, and 5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GV have a lower bleeding rate than esophageal varices, 3,4 but once ruptured, GV tend to bleed profusely as they have greater blood flow compared with esophageal varices. The cumulative risk for bleeding from gastric fundal varices is 16%, 36%, and 44% at 1, 3, and 5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16 Worsening of esophageal varices was seen in 27% of patients at 1 year and 58% at 3 years. 4 Therefore, esophageal varices should be followed every 6 months after BRTO. Worsening of ascites and hydrothorax has been seen post-BRTO.…”
mentioning
confidence: 99%
“…9,10,19,22,24 The second strategy was to use an adjunct sclerosant such as 50% glucose solution or absolute alcohol to keep the 5% ethanolamine oleate dose/volume to less than 40 mL. 4,8,17,19 Subsequently, American interventionalists introduced a new sclerosant: 3% Sotradecol, to perform the . This has caused some Japanese institutions to reconsider use of their ethanolamine oleate concoctions by mixing them with air to create a frothy consistency to the sclerosant with its desired sclerosant dose reduction (relative to volume) and the frothy percolative effect of the sclerosant.…”
Section: Conception and Evolution Of The Brto Proceduresmentioning
confidence: 99%
“…Although endoscopic variceal ligation therapy (EVL) has shown its benefit for esophageal varices, it cannot achieve a similar success in the management of gastric varices [6] . It was reported that balloon retrograde transvenous obliteration (B-RTO) is a useful treatment for gastric fundal varices, but it requires a gastrorenal shunt as the draining vein [7] . We report two cases of marked gastric varices with no gastrorenal shunt, who were successfully treated with endoscopic therapy with combined adhesives and sclerosants.…”
Section: Introductionmentioning
confidence: 99%